The intercultural and decolonial dialogue of knowledge in the training of indigenous teachers kaingang - Jorge Alejandro Santos; Cláudia Battestin; Daniel Berisso; Leonel Piovezana (Universidade Federal de Santa Catarina, 2019)
The  purpose of this paper is to present some of the stories and experiences of the training indigenous teachers of the kaingang people in the indigenous intercultural graduation by the Community University of the region of Chapecó - Unochapecó. We will state theoretical perspectives based on the Freirean pedagogy and the intercultural and decolonial perspective. Likewise, we will expose the difficulties and limits of the implementation of these perspectives in the daily educational practice. In this context, we will refer to how research allowed us to articulate solutions for some problems and articulate new perspectives for the future. Especially in areas where interculturality and decoloniality are more complex in its implementation, such as education in mathematics, science and new technologies. Finally, we believe that disseminating traditional culture and languages is a pedagogical instrument for the new generation of Indigenous Intercultural Teachers that are being formed in the Unochapecó. This is our challenge, to teach for diversity, interculturality and decoloniality, looking towards the times of resistance in which Latin America lives.